دور منهج حميدي في تعليم الخط العربي لطلاب المدرسة الخط القرأن بدينانيار جومبانج: دور منهج حميدي في تعليم الخط العربي لطلاب المدرسة الخط القرأن بدينانيار جومبانج - Nunik Zuhriyah; Syariful Ma’arif (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2023)
This research was motivated by the researchers' interest in the methods used to teach calligraphy at the Qur'an Calligraphy School in Denanyar, Jombang. In this school, calligraphy is taught using Manhaj Hamidy, a method of learning and teaching calligraphy that is relatively new in the world of calligraphy in Indonesia. However, although it is a new method of learning and teaching calligraphy (khath), this method has proven to make it easier for students to achieve targets. This research uses a phenomenological approach with qualitative methods. While the type of research used is a type of field research with observative steps, meaning that researchers must go directly into the field to find and make observations and can live directly about the actual situation so that it can also give meaning in the actual context. data collection techniques used observation, interview and documentation methods. The result of this study is that Manhaj Hamidy acts as an effective and efficient method of learning and teaching calligraphy as well as training and improving writing skills (maharah kitabah) in students at the Qur'an Calligraphy School (SAKAL) Denanyar Jombang.